The physiology of fetal membrane weakening and rupture: Insights gained from the determination of physical properties revisited. (June 2016) - Kumar, Deepak; Moore, Robert M.; Mercer, Brian M.; Mansour, Joseph M.; Redline, Raymond W.; Moore, John J.
Abstract: Rupture of the fetal membranes (FM) is precipitated by stretch forces acting upon biochemically mediated, pre-weakened tissue. Term FM develop a para-cervical weak zone, characterized by collagen remodeling and apoptosis, within which FM rupture is thought to initiate. Preterm FM also have a weak region but are stronger overall than term FM. Inflammation/infection and decidual bleeding/abruption are strongly associated with preterm premature FM rupture (pPROM), but the specific mechanisms causing FM weakening-rupture in pPROM are unknown. There are no animal models for study of FM weakening and rupture. Over a decade ago we developed equipment and methodology to test human FM strength and incorporated it into a FM explant system to create an in-vitro human FM weakening model system. Within this model TNF (modeling inflammation) and Thrombin (modeling bleeding) both weaken human FM with concomitant up regulation of MMP9 and cellular apoptosis, mimicking the characteristics of the spontaneous FM rupture site. The model has been enhanced so that test agents can be applied directionally to the choriodecidual side of the FM explant consistent with the in-vivo situation. With this enhanced system we have demonstrated that the pathways involving inflammation/TNF and bleeding/Thrombin induced FM weakening overlap. Furthermore GM-CSF production was demonstrated to be a critical common intermediate step in both the TNF and the Thrombin induced FM weakening pathways. This model system has also been used to test potential inhibitors of FM weakening and therefore pPROM. The dietary supplement α-lipoic acid and progestogens (P4, MPA and 17α-hydroxyprogesterone) have been shown to inhibit both TNF and Thrombin induced FM weakening. The progestogens act at multiple points by inhibiting both GM-CSF production and GM-CSF action. The use of a combined biomechanical/biochemical in-vitro human FM weakening model system has allowed the pathways of fetal membrane weakening to be delineated, and agents that may be of clinical use in inhibiting these pathways to be tested. Highlights: Fetal membranes undergo biochemically mediated weakening before rupture due to physical forces. Fetal membranes develop a para-cervical weak zone with collagen remodeling and apoptosis. TNF and Thrombin weaken fetal membranes with biochemical changes which mimic the physiological weak zone. GM-CSF is a critical common intermediate step in both TNF and Thrombin induced membrane weakening. Progestogens inhibit TNF, Thrombin and GM-CSF induced fetal membrane weakening.